When memory leads the brain to take scenes at face value: face areas are reactivated at test by scenes that were paired with faces at study - Walker, John A.; Low, Kathy A.; Cohen, Neal J.; Fabiani, Monica; Gratton, Gabriele (Frontiers in Human Neuroscience, 2014)
In the first use of the event related optical signal (EROS) as a brain imaging tool for the study of long-term memory, we examined relational or associative aspects of memory, widely presumed to involve the interplay among multiple brain regions in representing and reactivating different elements of a given event. Here, we found that a brain region known to be involved in face processing (the posterior superior temporal sulcus, STS) was active not only when viewing faces during the study phase but also when viewing scenes at test that, through prior learning, were associated with specific faces. These findings, demonstrating the activation of stimulus-specific cortical regions in the absence of stimuli of that type, based on learned relations, reveal cortical substrates of the reactivation of relational memories.